Respiratory responses and isocapnic buffering phase in child and youth soccer players during an incremental exercise test - Korkmaz Eryılmaz, Selcen; Karakaş, Selçuk; Boyraz, Cumhur; Günaştı, Özgür; Kılcı, Abdullah; Özdemir, Çiğdem; Özgünen, Kerem; Koç, Muhammed; Adaş, Ümit; Kurdak, Sadi (Frontiers in Physiology, 2024)
Purpose This study investigated the respiratory response and isocapnic buffering (IB) phase during an incremental exercise test to exhaustion in 16 child soccer players (11.9±0.9 years) and 18 youth soccer players (18.2±2.9 years). Methods The IB phase was calculated as the difference in oxygen uptake (VO2) between the respiratory compensation point (RCP) and metabolic threshold (MT) and expressed in either absolute or relative values. Results The maximal oxygen uptake (VO2max) was higher in youth players than in child players. For youth players, VO2max was measured at 55.9 ± 3.6 mL min−1 kg−1 and 74.9 ± 4.8 mL min−1 kg−0.75, while for child players, VO2max was 50.8 ± 4.1 mL min−1 kg−1 and 67.2 ± 6.1 mL min−1 kg−0.75 (p < 0.001). MT and RCP occurred at 69.8 ± 6.7% and 90.9 ± 6.9% of VO2max in child players and at 73.9 ± 5.1% and 91.5 ± 4.5% of VO2max in youth players, respectively. The two groups had no significant difference (p > 0.05). Absolute IB (10.6 ± 2.8 vs 9.7 ± 3.1 mL min−1 kg−1), relative IB (23.1 ± 5.7 vs 19.1 ± 6.1), and the ratio of RCP VO2 to MT VO2 (1.3 ± 0.09 vs 1.24 ± 0.09) were similar in child and youth players (p > 0.05). There was no difference in minute ventilation (V̇E, mL min−1 kg−1) and respiratory exchange ratio during exercise between the two groups (p > 0.05). During exercise, respiratory frequency, ventilatory equivalent for carbon dioxide (VE/VCO2) and oxygen (VE/VO2), VE/VCO2 slope, end-tidal O2 pressure were higher in child players than in youth players, while tidal volume (L kg−1), O2 pulse, and end-tidal CO2 pressure were lower (p < 0.05). Conclusion Despite differences in aerobic capacity and ventilatory response to exercise, child players showed similar IB phase as youth players. Although child players have lower ventilation efficiency than youth players, the higher ventilation response for a given VCO2 may provide an advantage in regulating acid-base balance during intense exercise.